Onset of hypertriglyceridemia in relation to dietary intake, gut microbiome and metabolomics signatures among home dwelling elderly - Hajar Fauzan, Ahmad; Mejia, Josue Leonardo Castro; Krych, Lukasz; Khakimov, Bekzod; Kot, Witold; Bechshøft, Rasmus Leidesdorff; Holm, Lars; Faust, Karoline; Engelsen, Søren Balling; Reitelseder, Søren (BMJ Publishing Group, 2020)
The human gut is home for plethora of microbes including prokaryotic, eukaryotic and other microorganisms. During ageing, imbalances in the gut microbiota are associated with significant phenotypic effects for the host such as the development of metabolic disorders like changes in serum lipids levels, including general physiological decline. However, the presence of fungal communities and their possible association with host health are poorly understood. Therefore, we aim to elucidate trajectory fo